A Study on the Role of Women’s Involvement in Fisheries and Aquaculture with Reference to the Mumbai Region - Chetan Panchal; Shivaji Pawar2 (International Journal of Marine Life, 2026)
Women play a crucial role in the fisheries and aquaculture sector, engaging in activities such as fish processing, marketing, and aquaculture management. Although they make major contributions, they frequently encounter socio-economic difficulties, such as limited access to funding, technological tools, and skill development opportunities. In the Mumbai region, women’s involvement in the fisheries industry is essential for economic sustainability, yet financial constraints and inadequate infrastructure restrict their growth and leadership opportunities. This research study explores the various prospects and obstacles encountered by women working in the fisheries and aquaculture industry. It explores how advancements in modern fish farming, value-added seafood processing, and government initiatives can enhance women’s participation. Furthermore, the research highlights the impact of policy interventions and skill development programs on improving women’s livelihoods. The study follows a mixed-method approach, incorporating both primary and secondary data. Primary data was collected through structured surveys from 100 fisherwomen in the Mumbai region, selected using convenience sampling. The survey used both closed-ended and open-ended questions to gather comprehensive data. The statistical analysis confirms that better working conditions, financial support, and access to modern tools positively impact women’s participation in fisheries. However, persistent challenges such as limited market access, lack of infrastructure, and limited access to technology continue to hinder their progress.
Keywords: Keywords: Aquaculture; Mumbai fisheries sector; economic empowerment; skill development; sustainable livelihoods; women in fisheries